The clinical case of treatment of apical granuloma (LLC "Endo Press", 2020)
The recent increase in the number of visits to dentists for the purpose of treatment and preservation of teeth. Thanks to new methods, tools and materials that appear in endodontic practice, the effectiveness of treatment of such teeth increases. The aim of this work is to establish a clear algorithm of treatment, to indicate the proper application of new methodologies